A Practical guide to hemiplegia treatment - Brahmachari, Ipsit (Jaypee Brothers Medical Publishers, 2015)
Hemiplegia, more commonly known as a stroke, is not just a neurological or a musculoskeletal condition, but one with a psychosocial impact on the patient's life. A Practical Guide to Hemiplegia Treatment addresses the physiotherapeutic management of hemiplegia focusing on the wider needs of the patient. This book is divided into various topics ranging from basic anatomy and physiology of the human brain and development of the nervous system, to clinical diagnosis, symptomology, and the management of hemiplegia complications. The essentials of rehabilitation medicine and approach to treatment are covered in detail. For quick reference, various exercises and treatment techniques are divided into lying, sitting and standing positions. Chapters on orofacial rehabilitation, perception, orthotics and management of complications provide a home care programme for hemiplegia patients. 55 images and illustrations enhance the information provided in this comprehensive guide to hemiplegia treatment.